Caracterização do nível de atividade física e aptidão física de mulheres diagnosticadas com câncer de mama - Buzaglo, Glenda Beatriz Brazão (Brasil, 2022)
In the Northern region of Brazil, breast cancer is one of the main causes of death among women. The aim of this study is to characterize the levels of physical fitness, physical activity and quality of life of women diagnosed with breast cancer. The study was conducted at the Oncology Control Center Foundation (FCECON) and evaluated 32 women diagnosed with stage I to III breast cancer. The assessment of physical activity was performed using the (IPAQ) for health-related physical fitness, the walking test was performed for a period of 6 minutes, lower limb strength through the sit and stand up test, and agility and balance through the Sit test, walk 2.44 m and sit again. Anthropometric variables were assessed using weight, height and waist circumference using a portable scale, stadiometer and measuring tape. The mean age of participants was 57±4.9 years 62.5% of the sample was classified as overweight. Regarding physical activity levels, it was found that most 93.8% did not meet the Brazilian recommendations for moderate- vigorous physical activity and 78.1% were classified as having very low physical fitness. Thus, the set of evidenced factors, associated with inactivity and low cardiorespiratory fitness strengthens the development of breast cancer, negatively contributing to treatment cycles and the quality of life of women diagnosed with breast cancer.